D-Day 80th anniversary [videorecording (DVD)] - Vigar, Bruce; Vigar, Bruce (Trinity Creative, 2024)
On June 6, 1944, the Allied Forces executed Operation Overlord, the largest seaborne invasion in history, storming the beaches of Normandy. The documentary explores this pivotal event, known as D-Day, which saw France and Western Europe liberated.